PENGARUH GREEN BRAND IMAGE, GREEN PERCEIVED VALUE, GREEN AWARENESS DAN GREEN KNOWLEDGE TERHADAP KEPUTUSAN PEMBELIAN - Tiara Apriliani; Diana Aqmala (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
The purpose of green marketing is to see that there is a concern for the environment, not merely seeing profit as the only goal. This study aims to find out the effect of green brand image, green perception value, green awareness, and green knowledge on purchasing decisions. The sample used was 105 users of The Body Shop. The method of data analysis used multiple linear regression and used SPSS analysis tools. The results show that green brand image, green perception value, green awareness, and green knowledge have a positive effect on purchasing decisions.